PENGARUH MEDIA PEMBELAJARAN INTERAKTIF BERBASIS SPEECH RECOGNITION TERHADAP KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS I SEKOLAH DASAR - Mahmudah, Alvi Ni’matul; Intan Susetyo Kusumo Wardhani; Wahyu Nugroho (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Early reading ability is a fundamental literacy competence for grade I elementary school students. Preliminary observations at SDN 2 Sukorejo, SDN 4 Sukorejo, and SDN 2 Gandusari showed that reading instruction was still dominated by conventional practices, while several students experienced difficulty recognizing letters, blending syllables, distinguishing similar phonemes, and reading simple words fluently. This study examined the effect and effectiveness of speech recognition-based interactive learning media on students’ early reading ability. The research used a quantitative quasi-experimental method with a nonequivalent control group design. The sample consisted of 44 students: 32 students in the experimental group from SDN 2 Sukorejo and SDN 4 Sukorejo and 12 students in the control group from SDN 2 Gandusari. Data were collected through oral performance tests administered as pre-test and post-test, then analyzed using descriptive statistics, prerequisite tests, Independent Samples T-Test, and N-Gain. The findings showed that the experimental group obtained a higher post-test mean score than the control group. The t-test result indicated a significant difference with Sig. (2-tailed) = 0.000 < 0.05. The experimental group obtained an N-Gain of 0.470, categorized as moderate, while the control group obtained 0.178, categorized as low. Thus, speech recognition-based interactive media significantly and more effectively improved students’ early reading ability compared with conventional learning.